Principles of computer security CompTIA Security+ and beyond, (exam SY0-501) - Conklin, Wm. Arthur; White, Gregory B.; Cothren, Chuck; Davis, Roger; Williams, Dwayne (McGraw-Hill, 2021)
Fully updated computer security essentials-mapped to the CompTIA Security+ SY0-601 exam Save 10% on any CompTIA exam voucher! Coupon code inside. Learn IT security fundamentals while getting complete coverage of the objectives for the latest release of CompTIA Security+ certification exam SY0-601. This thoroughly revised, full-color textbook covers how to secure hardware, systems, and software. It addresses new threats and cloud environments, and provides additional coverage of governance, risk, compliance, and much more. Written by a team of highly respected security educators, Principles of Computer Security: CompTIA Security+™ and Beyond, Sixth Edition (Exam SY0-601) will help you become a CompTIA-certified computer security expert while also preparing you for a successful career. Find out how to: Ensure operational, organizational, and physical security Use cryptography and public key infrastructures (PKIs) Secure remote access, wireless networks, and virtual private networks (VPNs) Authenticate users and lock down mobile devices Harden network devices, operating systems, and applications Prevent network attacks, such as denial of service, spoofing, hijacking, and password guessing Combat viruses, worms, Trojan horses, and rootkits Manage e-mail, instant messaging, and web security Explore secure software development requirements Implement disaster recovery and business continuity measures Handle computer forensics and incident response Understand legal, ethical, and privacy issues Online content features: Test engine that provides full-length practice exams and customized quizzes by chapter or exam objective Each chapter includes: Learning objectives Real-world examples Try This! and Cross Check exercises Tech Tips, Notes, and Warnings Exam Tips End-of-chapter quizzes and lab projects.
Title from content provider. - Available through AccessEngineering. - Description based on resource, viewed September 5, 2022
Keywords: Computer security -- Study guides -- Examinations; Computer networks -- Study guides -- Security measures -- Examinations; Sécurité informatique; Examens; Guides de l'étudiant; Réseaux d'ordinateurs; Sécurité; Mesures; Examens; Guides de l'étudiant; Computer networks; Security measures; Examinations; Computer security; Examinations; Study guides